Toxicity management and efficacy of carboplatin desensitization therapy for recurrent epithelial ovarian carcinoma: A real-world study. Issue 45 (11th November 2022) - Paksoy, Nail; Khanmammadov, Nijat; Doğan, İzzet; Ferhatoğlu, Ferhat; Yildiz, Anil; Ak, Naziye; Aydiner, Adnan
Abstract : Epithelial Ovarian cancer (EOC) is the most lethal gynecologic cancer worldwide. Carboplatin (CP) is the main chemotherapeutic agent in the treatment of ovarian cancer. However, the development of a hypersensitivity reaction (HSR) in 10% to 15% of patients with EOC is an important limiting factor for the clinical use of CP. Herein, we aimed to investigate the efficacy and safety of CP-desensitization (CP-D) therapy in the treatment of recurrent patients with EOC. Forty-seven ovarian cancer cases treated with CP-desensitization at the Istanbul University Oncology Institute were retrospectively analyzed between 01.01.2017 and 01.01.2022. The decision for CP-D was based on the patients' history of HSR and/or a positive skin test. For all patients, a 6-hour 12-step rapid drug desensitization protocol with a 30-minutes premedication regimen was used. Forty-seven patients were included in this study, and the median age at diagnosis was 53 years (range; 27–80). Twenty-one (43.7%) patients had 1 or more comorbid diseases, and 12.7% had a previous history of drug allergy. On average, HSR due to carboplatin was identified after 9 (7–16) cycles, and carboplatin was administered n = 11 (range, 3–36) times to patients. The overall survival from the first desensitization procedure (0S2) was 42.2 months (range: 25.3–59.1), and the 1-, 2-, and 5-years survival rates were 92.6%, 75.6%, and 47.2%, respectively. The objective response rate (ORR) was 78.5%. Cumulatively, 496 CP-D procedures were performed, of which 478 (96.3%) were successfully completed. None of the patients included in this study developed severe (grade 3–4) HSR during CP administration (no adrenaline was used, no need for intensive care). No deaths due to CP-D were noted. CP-D is a beneficial and safe method in treating platinum-sensitive recurrent EOC patients with CP-induced HSR.